Implentasi Scrum pada Pengembangan Aplikasi Sistem ADI STETSA SMAN 4 Malang: Bidang Unit Penjamin Mutu - Muhammad Syauqi; Aji Wibawa; Ilham Zaeni; Liliek Rahayu (Universitas Ngeri Malang, 2021)
The information system developed is called the Digital Studium et Sapientia Application (ADI STETSA). The development of this information system is a form of collaboration between the State Senior High School 4 Malang and the State University of Malang. The development of administrative services at State Senior High School 4 Malang is still manual. Therefore, an information system is needed. The purpose of developing the ADI STETSA information system in the field of Quality Assurance Unit (UPM) is to assist administrative data processing. The features developed in the UPM field are assignment decrees (SK) and UPM book materials. An information system developed on the website platform and the android operating system. The development of this information system uses the scrum method. This information system is carried out by ten people with divided teams. The work on the development of the academic information system was carried out in five sprints which were carried out in stages. This work is managed with the scrum framework which makes it more efficient. The results of the development of the ADI STETSA information system are information systems, Software Requirements Specifications (SKPL), and user manuals. Sistem informasi yang dikembangkan bernama Aplikasi Digital Studium et Sapienta (ADI STETSA). Pengembangan sistem informasi ini merupakan bentuk kerjasama antara Sekolah Menengah Atas Negeri (SMAN) 4 Malang dengan Universitas Negeri Malang. Pengembangan layanan administrasi di SMAN 4 Malang masih bersifat manual. Oleh Karena itu, dibutuhkan sistem informasi. Tujuan pengembangan sistem informasi ADI STETSA pada bidang Unit Penjamin Mutu (UPM) untuk membantu pengolahan data administrasi. Fitur yang dikembangkan pada bidang UPM yaitu surat keputusan (SK) tugas dan bahan buku UPM. Sistem informasi dikembangkan pada platform website dan sistem operasi android. Pengembangan sistem informasi ini menggunakan metode scrum. Sistem informasi ini dikerjakan oleh sepuluh orang dengan tim yang telah dibagi. Pengerjaan pengembangan sistem informasi akademik ini dilakukan lima sprint yang dilakukan bertahap. Pengerjaan ini dikelola dengan kerangka kerja scrum yang menjadikan lebih efisien. Hasil keluaran dari pengembangan sistem informasi ADI STETSA yaitu sistem informasi, Spesifikasi Kebutuhan Perangkat Lunak (SKPL), dan buku panduan penggunaan.